Analisis Yuridis Terhadap Asas Efisiensi Berkeadilan Berdasarkan Pasal 33 Ayat (4) UUD 1945 Dalam Peraturan Perundang-undangan Di Bidang Ketenagalistrikan - Anugroho, Adhi; Lestarini, Ratih; Hayati, Tri (Jurnal Hukum & Pembangunan, 2017)
This thesis discusses the implementation of the principle of "equitable efficiency" as contained in Article 33 paragraph (4) of the 1945 Constitution After the 4th Amendment in legislations concerning electricity. This research analyzes how the Constitutional Court interprets the element of "equitable efficiency" in the constitutional reviews Electricity Law. This article concludes that the meaning of "equitable efficiency" in Article 33 paragraph (4) of the 1945 Constitution After the 4th Amendment is that the national economy should be organized to use the least amount of resources to achieve the greatest amount of welfare which could be enjoyed equitably by the all citizens. In regards to Indonesia's electricity sector, it was found that each electricty regulation has embodied at least one aspect of the principle of "equitable efficiency".